Masalah Menyusui sebagai Determinan Terjadinya Risiko Depresi Postpartum pada Ibu Nifas Normal: The Breastfeeding Problem as Determined of Postpartum Depression Risk - Sukma, Febi; Revinel, Revinel (Jurnal Bidan Cerdas, 2020)
Postpartum women who had mild postpartum depression range from 10/1000 live births and moderate/severe postpartum depression ranging from 30-200 /1000 live births. This study aims to analyze factors that influence the risk of postpartum depression in postpartum mothers. Research Methods: This research is a quantitative study with a cross-sectional design. The population in this study were postpartum women aged 2-6 weeks with 121 respondents, selected by two-stage Cluster sampling, followed by random sampling. The research was conducted at the primary health center in Central Jakarta area using the Edinburgh Postpartum Depression Scale (EPDS) questionnaire. It was found that mothers who had breastfeeding problems had a greater risk of developing postpartum depression (OR; 39.3), the greater the husband's support, the lower the risk of postpartum depression (OR; 0.13), and it was found that lower-income resulted in a greater risk of depression postpartum (OR; 14.7). In conclusion, the risk of post-partum depression is influenced by three factors: breastfeeding, husband support, and income. Of the three factors, the more dominant cause of postpartum depression risk is breastfeeding problems.